A Middle-Aged Female with Multiple Brownish Plaques and Nodules: A Case Report of Multiple Cutaneous Reticulohistiocytomas - Sijapati, Karuna Singh; Karki, Sudha; Karki, Smriti (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Non-Langerhans-Cell histiocytosis spectrum of disorders includes multicentric reticulohistiocytosis (MR) and multiple cutaneous reticulohistiocytomas (MCR), which are very uncommon granulomatous conditions. In reticulohistiocytoma, the most common sites of involvement are extensor surfaces, particularly the hands and forearms and the classical lesions are characterised by firm brown or yellow papules, nodules and plaques. As MCR is a very rare granulomatous condition, we report here a middle-aged female a case of MCR and we highlight the significance of considering reticulohistiocytoma in the differential diagnoses of chronic and persistent brownish plaques or nodules on skin.